STEM Based Student Worksheets to Improve Ecosystem Material Critical Thinking - Pinkan Deviana Khairunnisa; Indayana Febriani Tanjung (Jurnal Pedagogi dan Pembelajaran, 2023)
The development of STEM-based LKPD is manifested in high school learning media which cannot help improve the critical thinking skills of class X students. Students' low critical thinking ability impacts learning outcomes that could be more optimal. The purpose of this research is to develop STEM-based worksheets to improve critical thinking skills that are feasible, practical and effective. 4D development research model (define, design, develop, disseminate). Collecting data with the method of observation, interviews and questionnaires. The instrument used in collecting data is a questionnaire sheet. Data analysis techniques with quantitative and qualitative analysis. The test subjects were 22 graders. Quantitative data analysis is used to see the validity, practicality and effectiveness of LKPD. Qualitative analysis is used to see suggestions, revisions and observation results. The results of the LKPD research were declared valid based on the assessment results by 2 experts, namely media experts 92.3% and material experts 91%, with a very valid category. LKPD was stated to be practical with the results of teacher and student responses through the channel, namely 100% teachers and 99.24% students with a very practical category. LKPD is also effective for improving critical thinking skills seen from the average N-Gain result of 0.92 in the effective category. It was concluded that STEM-based LKPD could improve students' critical thinking skills.